The Contribution of UIN SATU Tulungagung to MSME Welfare in Plosokandang Village: An Islamic and Positive Law Perspective - Indah Febriana, Nina; Nanda Putri Pangestu, Khofifah (El-kahfi | Jurnal Ekonomi Islam, 2025)
The contribution of higher education institutions to the development of micro, small, and medium enterprises (MSMEs) plays a strategic role in enhancing community welfare and strengthening the local economy. This study investigates the involvement of UIN Sayyid Ali Rahmatullah (UIN SATU) Tulungagung in supporting MSMEs in Plosokandang Village, Tulungagung Regency, from both Islamic and positive (national) legal perspectives. Using a descriptive qualitative method, data were collected through field observations, in-depth interviews with 15 MSME actors, and analysis of relevant documents and literature. The findings show that the university contributes through business training, student internships, mentoring programs, and market access facilitation. Concretely, 73.3% of respondents reported increased monthly income by 15–25% after engaging in campus-supported activities. From an Islamic law standpoint, these efforts reflect the values of ta’awun (mutual assistance) and maslahah (public benefit), while from the perspective of positive law, they align with the tri dharma of higher education, particularly community service. In conclusion, UIN SATU’s active role in MSME empowerment is well-grounded in both Islamic and national legal frameworks and significantly contributes to local economic resilience